The Effect of Work Ethics on Employee Performance CV. Gaza Perdana Palembang - Ego Goper; Muhammad Wadud; Susi Handayani (International Journal of Marketing & Human Resource Research, 2023)
This study aims to analyze the effect of work ethic on employee performance CV. Gaza Perdana Palembang. Data collection techniques were carried out by distributing questionnaires and interviews. The sample used in this study was 37 employees. The data analysis technique used is Simple Linear Regression Analysis, t-test, and Coefficient of Determination Analysis. The results showed that there was a positive and significant effect of work ethic on employee performance. The results show the value of the Correlation Coefficient (R) is 0.401 which shows the relationship between work ethic and employee performance is 40.1%. Furthermore, research using the analysis of the coefficient of determination (R2) obtained a value of 0.161, this value means that the contribution and influence of the work ethic variable on employee performance is 16.1%.